2018
DOI: 10.1105/tpc.17.00420
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Nod Factor Hydrolase MtNFH1 in Regulating Nod Factor Levels during Rhizobial Infection and in Mature Nodules of Medicago truncatula

Abstract: Establishment of symbiosis between legumes and nitrogen-fixing rhizobia depends on bacterial Nod factors (NFs) that trigger symbiosis-related NF signaling in host plants. NFs are modified oligosaccharides of chitin with a fatty acid moiety. NFs can be cleaved and inactivated by host enzymes, such as MtNFH1 (MEDICAGO TRUNCATULA NOD FACTOR HYDROLASE1). In contrast to related chitinases, MtNFH1 hydrolyzes neither chitin nor chitin fragments, indicating a high cleavage preference for NFs. Here, we provide evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 88 publications
4
32
2
1
Order By: Relevance
“…TtsI is the transcriptional activator of T3SS genes and effector genes, including nopP, and can be transcriptionally induced by the NodD1-flavonoid complex (38,39), which can also activate the transcription of nod genes involved in the biosynthesis of Nod factors (NFs). Although rhizobial NFs are the key symbiotic signal initiating both infection and nodule organogenesis (40), it was recently demonstrated that excess amounts of NFs negatively regulate the initiation of infection threads in M. truncatula, and NF hydrolase MtNFH1 is involved (41). The abnormal branching of indeterminate nodules, as seen on MtNFH1-deficient M. truncatula plants, was also observed on C. cajan roots inoculated with mutants lacking znu genes of CCBAU45436 in this study.…”
Section: Discussionsupporting
confidence: 58%
“…TtsI is the transcriptional activator of T3SS genes and effector genes, including nopP, and can be transcriptionally induced by the NodD1-flavonoid complex (38,39), which can also activate the transcription of nod genes involved in the biosynthesis of Nod factors (NFs). Although rhizobial NFs are the key symbiotic signal initiating both infection and nodule organogenesis (40), it was recently demonstrated that excess amounts of NFs negatively regulate the initiation of infection threads in M. truncatula, and NF hydrolase MtNFH1 is involved (41). The abnormal branching of indeterminate nodules, as seen on MtNFH1-deficient M. truncatula plants, was also observed on C. cajan roots inoculated with mutants lacking znu genes of CCBAU45436 in this study.…”
Section: Discussionsupporting
confidence: 58%
“…Downstream of the Nod factor signaling pathway, paralogous Nod factor hydrolases MtNFH1 (NOD FACTOR HYDROLASE1) and LjCHIT5 (CHITINASE5) cleave the lipochitooligosaccharidic backbone of Nod factors produced by their respective symbionts ( Figure 3). This degradation of Nod factors appears to be crucial for rhizobial infection, colonization, and nodule formation (Cai et al, 2018;Malolepszy et al, 2018). Interestingly, delays in nodule formation by aberrant Nod factor-producing strains were abolished in Ljchit5 mutants, implicating Nod factor hydrolysis in partner recognition (Malolepszy et al, 2018).…”
Section: Nod Factor Signaling and The Common Symbiotic Pathwaymentioning
confidence: 99%
“…Regulation of LCO perception involves their degradation by host hydrolases in the rhizosphere and symbiotic tissues (Tian et al, 2013;Cai et al, 2018;Malolepszy et al, 2018). This might explain why diverse doses of LCOs trigger similar symbiotic responses and Fig.…”
Section: Differential Immunity Suppression By Lcos In Symbiotic and Nmentioning
confidence: 99%